The Developmental Conditions of Classroom Teaching and Learning in a Primary School in Zimbabwe - SIBONOKUHLE NIL Ndlovu; Azwihangwisi E. Muthivhi (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2013)
The paper bases upon the research that was carried in 2010 to investigate the prevailing conditions of schooling and classroom teaching and learning in Southern Zimbabwe, using the Vygotskian socio-cultural theory to analyse the consequences that the breakdown of schooling and classroom teaching and learning had on learners'performance and cognitive development. Using a case study of the specific primary school in Gwanda district, the findings were that classroom teaching and learning in rural Zimbabwe was adversely affected by a conglomerate of contextual factors and worsened by the prevailing socio-economic and political problems resulting in contradictory classroom practices of teaching and learning. The analysis revealed the extent to which classroom teaching and learning had deteriorated and how the cultural practices of this specific tradtion of schooling impede on the possibilities for meaningful learning activities in the classroom. The paper contributes towards an understanding of the effects of the specific cultural conditions of schooling on learners' learning and cognitive development within the prevailing context of socio-economic and political instability in Zimbabwe and suggests ways in which teachers could organise pedagogy to assist their learners' learning and cognitive development.